The role of uncharacterized protein Taf1 in regulating ATP levels and virulence of Cryptococcus neoformans - Yuanyuan Ma; Kaisu Pan; Ling Shen; Jianhua Qu; Yu Han; Cunwei Cao; Peng Xue (BMC Microbiology)
Abstract The human fungal pathogen Cryptococcus neoformans poses significant health risks, particularly to immunocompromised individuals, such as those with HIV/AIDS. In this study, we investigate the role of an uncharacterized protein, Taf1, in regulating ATP levels and virulence in C. neoformans. Our previous proteomic analyses confirmed the expression of Taf1, encoded by the gene CNAG_04232. We found that the deletion of the TAF1 gene resulted in the upregulation of 204 genes and the downregulation of 908 genes. Gene Ontology analysis indicated that these regulated genes are associated with metabolic and cellular processes, as well as ATP-dependent activities. Notably, the TAF1-deficient mutant exhibited impaired growth at elevated temperatures (39°C). Furthermore, in a murine model of infection, mice inoculated with the taf1Δ mutant demonstrated significantly improved survival compared to those infected with the wild-type strain, suggesting a critical role for Taf1 in virulence. Additionally, KEGG pathway analysis of RNA-Seq and metabolomics data revealed significant alterations in fatty acid biosynthesis and degradation pathways following TAF1 deletion. Collectively, these findings underscore the essential role of Taf1 in modulating cellular energy and its implications for the virulence of C. neoformans, thereby paving the way for potential therapeutic strategies targeting this pathogen.